Penerapan Activity Based Costing untuk Efisiensi Biaya Produksi dan Profitabilitas Petani Ubi Kayu - Diah Agustiana; Berwin Anggara; Carmidah Carmidah (Jurnal Proaksi, 2025)
Main Objective - This study evaluates the application of Activity Based Costing (ABC) to reduce production costs and increase the profitability of cassava farming, while also comparing the disparities between farmers with owned land and leased land. Method - The research employs a descriptive qualitative approach with purposive sampling techniques. Data were obtained through interviews, documentation, and secondary sources. The analysis was carried out by identifying production activities, determining cost drivers, calculating activity costs using the ABC method, and comparing farmer profitability based on land ownership. Main Finding - The results show that the ABC method is able to provide a more detailed and efficient calculation of production costs. Production costs on owned land were recorded at IDR 13,035,000/ha with a cost of production of IDR 434.5/kg, while on leased land they reached IDR 21,035,000/ha with a cost of production of IDR 701/kg. The main difference is due to the significant land rental burden, resulting in a net profit margin of 56% for land-owning farmers, compared to 30% for tenant farmers. Theory and Practical Implications - The application of ABC is relevant for agricultural cost efficiency and can serve as a basis for extension policies. Novelty - This study enriches the agricultural accounting literature by highlighting the disparities in costs and profitability in cassava farming. Keywords: Activity Based Costing, Production Cost Efficiency, Cost of Production, Farmer Profitability, Cassava